Absence of transitive and systemic pathways allows cell-specific and isoform-specific RNAi in Drosophila - ROIGNANT, JEAN-YVES (Copyright 2003 by RNA Society, 2003)
RNA interference (RNAi) designates the multistep process by which double-stranded RNA induces the silencing of homologous endogenous genes. Some aspects of RNAi appear to be conserved throughout evolution, including the processing of trigger dsRNAs into small 21–23-bp siRNAs and their use to guide the degradation of complementary mRNAs. Two remarkable features of RNAi were uncovered in plants and Caenorhabditid elegans. First, RNA-dependent RNA polymerase activities allow the synthesis of siRNA complementary to sequences upstream of or downstream from the initial trigger region in the target mRNA, leading to a transitive RNAi with sequences that had not been initially targeted. Secondly, systemic RNAi may cause the targeting of gene silencing in one tissue to spread to other tissues. Using transgenes expressing dsRNA, we investigated whether transitive and systemic RNAi occur in Drosophila. DsRNA-producing transgenes targeted RNAi to specific regions of alternative mRNA species of one gene without transitive effect directed to sequences downstream from or upstream of the initial trigger region. Moreover, specific expression of a dsRNA, using either cell-specific GAL4 drivers or random clonal activation of a GAL4 driver, mediated a cell-autonomous RNAi. Together, our results provide evidence that transitive and systemic aspects of RNAi are not conserved in Drosophila and demonstrate that dsRNA-producing transgenes allow powerful reverse genetic approaches to be conducted in this model organism, by knocking down gene functions at the resolution of a single-cell type and of a single isoform.